Proses Pembuatan Fabric Manipulation Dengan Teknik Tucking Menggunakan Kain Denim Pada Croptop - Arina Haq; Irmatul Afizah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
The sewing techniques in clothings can be added as a value for the beauty of clothing. This research uses fabric manipulation techniques. Fabric manipulation is a technique of manipulating textile materials by using the technique of decorating fabrics to form new textiles. This writing aims to knowing the process of making tucking techniques using denim fabric on a croptop. Tucking technique is a fold that reduces the size of the fabric, it is usually folded in one direction or another. Method used in this paper is a qualitative method. The process of fabric manipulation with tucking technique using the denim fabric begins by determining the tucking technique that will be used. The tucking techniques used are pin tucks, bow-tied tucks and undulating tucks. After determining the technique that will be used, then prepare the tools and materials. The conclusion of the process of making fabric manipulation with the tucking technique using denim fabric on the croptop is that tucking is made with great care in the measurement of each fold so that the results are accurate. The use of denim fabric with tucking technique can form the appropriate wave, the great is caused to make it look neater and less wrinkled. In the tucking process, you must pay attention to the fabric needs, so that when folded it is according to the pattern and it should be marked so that it does not slide the folds. The choice of material should be considered well in the making of tucking, because the thickness of the material and the the composition of the material greatly affects the result of the tucking wave.